DAMPAK PERKEMBANGAN TEKNOLOGI PENINGKATAN KUALITAS PENDIDIKAN - Ade Sofyan; Amin Hidayat (FAKULTAS TEKNIK, 2022)
Influence of Technology for Education. As time goes by technology in the world of education has experienced various developments, where everything has used technology to facilitate all its work, including in the world of education as now the increasing number of vocational high schools being built is proof that educational technology in Indonesia is increasingly advanced because vocational schools use tools and media in carrying out learning that is done at school. Technology becomes a supporting tool used in education to make it easier for teachers to teach students with the results to be achieved. In times like today we often encounter the use of technology in the implementation of learning carried out by an educator to teach or students or students to learn. However, in the development of modern technology, it can also not only have a positive impact on education, but also have a negative impact on behavioral changes carried out by students which can damage norms, educational rules, and morals in social life